The Relationship Between Multiple Roles Of Working Mothers And Their Family Life Satisfaction Within The Banking Sector In Ghana - Asante-Twum, C. (University of Ghana, 2014)
Women in the Ghanaian society have always worked to support and take care of their families. Their work however mostly took place in the informal sector in recent times however; Ghanaian women have had to combine traditional roles with formal employment, a phenomenon which has dire implications on both the women and their families. The study investigated and sought to establish the relationship between multiple roles of working mothers and their family life satisfaction within the banking sector in Ghana. Multiples roles were examined from the perspective of paid work demands, household chores, conjugal duties, and childcare activities. A quantitative design was employed using the survey approach. Data were collected using a self-administered questionnaire targeting basically working mothers in the banking sector who are married with at least one child under the age of 10 years living at home as respondents. Logistic regression analyses was used to identify reporting time at work, number of minutes it takes to get home, washing of clothes, cleaning the home, cooking, sharing intimate moments with husband, preparing children for school, and assisting children with homework as significant correlates of family life satisfaction. These factors reliably distinguished between working mothers who are satisfied and those who are not satisfied with their family life. These factors are discussed in terms of contextual literature on how these variables affect working mothers’ family life satisfaction. These findings provide evidence that the working mothers need assistance in order to meet their multiple role demands. Hence, implications of the findings for policy and practice, such as the need to give working mothers with younger children flexible working hours, establish family support programs and develop national work-family balance policy, are discussed.
Thesis (MPhil)
Keywords: Relationship; Multiple Roles; Family Life Satisfaction; Banking Sector; Ghana